EXAMINING AUGMENTED REALITY ON PURCHASE INTENTION THROUGH TECHNOLOGY ACCEPTENCE MODEL - Zulfi Atika Dewi; Tri Wismiarsi; Bambang Purwoko Kusumo Bintoro (Jurnal Scientia, 2023)
The increasing number of smartphone and internet users has made Indonesia a potential country to develop digital technology. Digitalization drives marketplaces in Indonesia larger than before, and this increases competition. Augmented Reality (AR) is a form of increasing competition in the retail industry. AR is an interactive technology that combines the real world with the virtual world, then projected at the same time. Since AR is a new digital application, so the use of this application is still limited. Sephora is one of few companies that has applied AR technology in its application. This is why this study looks at the effect of AR technology, especially its mediation effect on Technology Acceptance Model (TAM) and purchase intention. This research is a quantitative study. The number of respondents for this research is 200. Structural Equation Model (SEM)-PLS (partial least square) was used to analyse data collected through a digital survey. The results show that all dimensions of Technology Acceptance Model, except ease of use, have a positive and significant effect on purchase intention. This depicts that, a relatively new technology must benefit the consumers. In addition, technology acceptance model (TAM) significantly mediates the relationship between augmented reality and purchase intention.